What is meant by ‘adequate supervision’ under the Tax Agent Services Act 2009 for individuals employed by a Partnership or a Company providing Tax Agent services? - Mc Laren, John Andrew; Fullarton, Lex (Australasian Tax Teachers Association, 2025)
The current measures of adequate supervision of tax agent practice staff are akin to having road traffic laws in place to ensure intoxicated drivers are apprehended and kept off our highways, but without a police force to detect and enforce those laws. However, to have a TPB without the necessary resources to detect and enforce proper professional practice and the close supervision of unregistered staff is exactly where we find ourselves. We strongly recommend that an investigative organisation be established and a clear definitions of 'satisfactory supervision' be determined. We point to a raft of similar regulated professions and industries that require a suitably qualified person to always be present while the enterprise is operating - hotels; motor vehicle dealers; real estate and settlement agencies; legal practices and so on.